Prospective Electromechanical Control Systems of Industrial Manipulator Efforts - Nikolay Alexandrovich Sukhenko; Georgiy Yakovlevich Pyatibratov; Anzhela Alexandrovna Danshina; Lermont Lyevikovich Altunyan (Institute of Advanced Engineering and Science, 2016)
The current electric drive of industrial manipulators is implemented on the principle of speed control and position of the actuator, often do not provide actuator motion as consistent with required process specifications. Taking into account the disadvantages of existing control systems the new approach to control systems engineering and implementation of industrial manipulators electric drives using force balancing systems of actuator efforts control was proposed. Application properties and implementation of efforts control systems inside springy gears and mechanisms of industrial manipulators have been studied. The efficient structure of electromechanical system, which provides the desired balance the transfer object weight and dampening of manipulators mechanical gears springy oscillations is proved. The studies were performed on mathematical modeling and the prototype of industrial manipulators, which confirmed the performance of control system potential structure application and synthesized effort regulator which provide the required performance factor. The potential electromechanical force balancing systems is ably to increase industrial manipulators performance quality, provides transfer and the desired positioning of load directly by operator. Possibility of efficient application the scope increase of industrial manipulators using the potential force balancing systems of efforts control is defined.